Role of innovation and architectural marketing capabilities in channelling entrepreneurship into performance - María Leticia Santos Vijande; José Ángel López Sánchez; Enrique Loredo; John M. Rudd; Nuria López-Mielgo (Journal of Innovation & Knowledge (JIK), 2022)
Entrepreneurial orientation (EO) is associated with superior performance, although the mechanisms through which EO translates into an advantageous market position are still poorly understood. Drawing on EO and resource-based theory (RBT) literature, this study highlights the role of a systemic bundle of firms' capabilities in channelling the effect of EO on performance. The components of EO - innovativeness, risk-taking, and proactiveness - are analysed hierarchically to better understand how the entrepreneurial process builds within the firm and facilitates the development of idiosyncratic capabilities. The results, based on a sample of firms operating in rapidly evolving markets, suggest that innovativeness, as part of the organizational culture, contributes to risk-taking and proactiveness. Proactiveness enables firms to seize new market opportunities and foster innovation capability, directly and indirectly, through networking and market learning. Innovation capability is the ultimate driver of a firm's performance, in terms of enhancing its customer equity and business growth.
Keywords: M10; M13; M14; M30; M39; O31; 650; Entrepreneurial orientation; Firm performance; Hierarchical model; Innovation capability; Market learning; Networking